THE INFLUENCE OF LEADER–MEMBER EXCHANGE AND SELF EFFICACY ON VOICE BEHAVIOR THROUGH PSYCHOLOGICAL OWNERSHIP OF NURSES AT ARTHA BUNDA HOSPITAL, CENTRAL LAMPUNG - Ni Wayan Siska Anggraeni; A. Rohendi A. Rohendi; Yuniati Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Nurses represent the largest group of healthcare professionals and are the most frequently involved in direct interactions with patients, making their ability to communicate effectively and express constructive opinions essential for improving service quality and ensuring patient safety. Voice behavior refers to the willingness of individuals to convey ideas, feedback, or suggestions that contribute to organizational improvement. However, this behavior is not always optimally demonstrated by nurses and can be influenced by leader member exchange, self-efficacy, and psychological ownership. This study aimed to analyze the effects of leader member exchange and self efficacy on nurses’ voice behavior, with psychological ownership as a mediating variable. The research employed a quantitative, cross-sectional design. Data were collected using questionnaires distributed to nurses at ARTHA BUNDA Hospital, Central Lampung, with a total of 35 respondents selected based on inclusion criteria. Data analysis included simple linear regression, multiple linear regression, and mediation tests. Results show that both leader member exchange and self efficacy have positive and significant effects on psychological ownership, with leader member exchange showing a moderate effect and self-efficacy demonstrating a strong effect. Additionally, leader member exchange and self efficacy each have positive and significant effects on voice behavior, though the effect sizes range from low to moderate. Psychological ownership also positively influences voice behavior but with a low effect. However, psychological ownership does not significantly mediate the relationship between leader member exchange or self efficacy and voice behavior. This is attributed to the form of psychological ownership that emerges, which is more preventive (territorial) rather than promotive. Therefore, hospitals should cultivate promotive psychological ownership to encourage more active voice behavior among nurses.